Preception of Polytechnic Teachers on Industry Institute Interaction-A Study - Mittal, L. N. (Journal of Engineering Education Transformations, 1992)
The paper highlights the need for industry institute linkage and presents the perceptions of polytechnic teachers on industry-institute interaction. In the ultimate analysis, the paper presents a scheme of education-work linkage for offering generalized diploma courses in civil, electrical and mechanical engineering.